2012
DOI: 10.1159/000337910
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic-Induced Hyperprolactinemia and Testosterone Levels in Boys

Abstract: Aims: This cross-sectional study investigatesthe effect of antipsychotic (AP)-induced hyperprolactinemia on testosterone, luteinizing hormone (LH), follicle-stimulating hormone (FSH), inhibin B, and puberty in boys with mainly autism spectrum disorders (ASD). Method: One hundred and four physically healthy 10- to 19-year-old boys with ASD or disruptive behavior disorder (DBD) were recruited between October 2006 and November 2009. Fifty-six adolescents had been treated with AP for >16 months; 48 had never been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Similar results have reported that long-term hyperprolactinemia could cause the suppression of the hypothalamic-pituitary gonadal axis and a decrease in the levels of gonadotropin-releasing hormone, LH and T in males 42. Recently, Roke et al 43. reported that boys with antipsychotic-induced hyperprolactinemia had obviously lower T levels than male adolescents with normal PRL levels.…”
Section: Discussionsupporting
confidence: 69%
“…Similar results have reported that long-term hyperprolactinemia could cause the suppression of the hypothalamic-pituitary gonadal axis and a decrease in the levels of gonadotropin-releasing hormone, LH and T in males 42. Recently, Roke et al 43. reported that boys with antipsychotic-induced hyperprolactinemia had obviously lower T levels than male adolescents with normal PRL levels.…”
Section: Discussionsupporting
confidence: 69%
“…This suggests that hyperprolactinemia may inhibit bone turnover, possibly by a direct negative effect on osteoblasts, or by a secondary effect through hyperprolactinemia-induced hypogonadotropic hypogonadism. We have reported before that the boys with hyperprolactinemia had significantly lower testosterone levels (52), which may have resulted in a decrease in bone turnover. Further research in this area is needed as bone turnover markers reflect the dynamic aspect of bone metabolism, and longitudinal data are needed to investigate the changes over time.…”
Section: Biochemical Bone Markersmentioning
confidence: 90%
“…All participants were recruited from the total patient population of the outpatient adolescent clinic of the GGz Central Psychiatric Centre, the Netherlands, from October 2006 to November 2009 [12,27]. All participants had a diagnosis of ASD or DBD.…”
Section: Participantsmentioning
confidence: 99%